Studies on Pseudodendrothrips (Thysanoptera, Thripidae) from India, with one new species - Rachana, R.r.; Amarendra, B.; Gracy, R. Gandhi (Zootaxa, 2022)
Pseudodendrothrips umbrolateralis sp. n. is described from India. An identification key to the seven Pseudodendrothrips species recorded from India is provided. The earlier record from India of P. bhattii Kudo is considered a misidentification of P. darci (Girault) and hence, is removed from the fauna of India.